Analisis Sanksi Cambuk Bagi Pelaku Prostitusi Berdasarkan Qanun Aceh Nomor 06 Tahun 2014 Tentang Hukum Jinayat Ditinjau Dari Sisi Hak Asasi Manusia: Analisis Sanksi Cambuk Bagi Pelaku Prostitusi Berdasarkan Qanun Aceh Nomor 06 Tahun 2014 Tentang Hukum Jinayat Ditinjau Dari Sisi Hak Asasi Manusia - Nila Afiati; Uthman Shehu Lawal (Yapilin Press, 2025)
This research focuses on the legal, philosophical, and human rights analysis of the application of caning sanctions in prostitution crimes as regulated in Aceh Qanun Number 06 of 2014. The study is directed to examine the legal legitimacy, social effectiveness, and normative tensions between sharia norms and human rights principles in the context of Aceh's special autonomy. The research method used is a normative legal approach, with a review of legislation, legal doctrine, and academic literature. The analysis was conducted qualitatively through content analysis methods to assess the consistency, relevance, and consequences of the application of caning sanctions. The results show that caning sanctions in Aceh have strong legal legitimacy through the constitution, UUPA, and Qanun Jinayat, and are based on philosophical values ​​​​of justice, welfare, and deterrent effects. However, its effectiveness in suppressing prostitution practices is still limited due to more dominant socio-economic factors. From a human rights perspective, caning creates normative tensions because it has the potential to violate the principle of prohibition of torture and treatment that degrades human dignity. The implications of this research emphasize the importance of reformulating Aceh's criminal justice policy to be more adaptive to human rights criticisms without neglecting the legitimacy of sharia. This effort can be achieved through regulatory evaluation, strengthening empirical indicators of deterrent effects, and exploring more humane alternatives to sharia-based punishment.